2006
DOI: 10.1007/s10560-006-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Differences in Offending Patterns: Examining Family Group Conferencing Interventions among At-Risk Adolescents

Abstract: This secondary study looked at the importance of ethnicity and gender in influencing the relationship between Family Group Conferencing and (FGC) recidivism. The FGC is a mediation procedure involving offenders, their families, and victims of their crimes in which outcomes of material and emotional restitution are sought. Offenders, randomly sampled to participate in a control or experimental group, were sampled via mail, telephone, and in-person interviews. Data from court records were utilized to obtain reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…In general, males are more likely to recidivate than females (e.g., Baffour, 2006;Dembo, Schmeidler, Nini-Gough, Sue, Borden, & Manning, 1998;Minor, Hartmann, & Terry, 1997;Schwalbe, Fraser, Day, & Cooley, 2006; but see Benda, Corwyn, & Toombs, 2001). Race and ethnicity are also associated with recidivism, such that individuals who are of a minority race or ethnicity are at greater risk of recidivism (e.g., Dembo et al, 1998;Minor et al, 1997;Schwalbe et al, 2006; but see Baffour, 2006). Age has also been associated with recidivism (e.g., Minor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In general, males are more likely to recidivate than females (e.g., Baffour, 2006;Dembo, Schmeidler, Nini-Gough, Sue, Borden, & Manning, 1998;Minor, Hartmann, & Terry, 1997;Schwalbe, Fraser, Day, & Cooley, 2006; but see Benda, Corwyn, & Toombs, 2001). Race and ethnicity are also associated with recidivism, such that individuals who are of a minority race or ethnicity are at greater risk of recidivism (e.g., Dembo et al, 1998;Minor et al, 1997;Schwalbe et al, 2006; but see Baffour, 2006). Age has also been associated with recidivism (e.g., Minor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Daly and Stubbs (2006) critically note the absence of gender in discussions of the RISE finding, but other studies suggest that girls may benefit even more than boys from restorative programming. Baffour's (2006) study of family group conferencing demonstrated greater reduction in recidivism for female offenders as compared to their male counterparts. Rodriguez's study (2007) found that girls and juveniles with minimal criminal history records had the most success from participating in RJ programs.…”
Section: Gender-responsive Programmingmentioning
confidence: 92%
“…Mediation has a rich cultural heritage and draws upon various indigenous problemsolving techniques (Baffour, 2006). Its formalisation in restorative justice in the 1980s stems from the traditional conflict-resolution techniques of the Maori in New Zealand and in Indian communities in North America (Zehr, 2004).…”
Section: Development Of Restorative Justicementioning
confidence: 99%
“…However, these studies are often marred by small sample sizes, lack of representation of study populations, absence of experimental controls, and non-comparable definitions of recidivism. In addition, many studies focus on process measures, in particular experiences of fairness and restoration, without considering outcomes such as recidivism (Baffour, 2006;Bergseth & Bouffard, 2007;Bonta, Wallace-Capretta, Rooney & McAnoy, 2002;McCold & Wachtel, 2000). It is also important to keep in mind that results are influenced by self-selection bias, since programmes are voluntary and participants may be more motivated to ensure positive outcomes (Hudson, 2002;Latimer, Dowden & Muise, 2005).…”
Section: Evidence On the Outcomes Of Restorative Mediationmentioning
confidence: 99%
See 1 more Smart Citation